Mikrofom sebagai sumber warisan - Pauziaah, M.; Sinnasamy, J.; Mohd Zailan, Endin (University of Malaya Library, 2009)
This paper describes the steps taken by the University of Malaya Library to implement the continual improvement project for the year 2008/2009, entitled “Microform as a Source of Heritage”. This project is to fulfill the requirement of MS ISO 9001:2000 standard under clause 8.5.1 of the Malaysian Standard (2000). The clause states that the organization shall continually improve the effectiveness of the quality management system through the use of the quality policy, quality objectives, audit results, analysis of data, corrective and preventive action and management review. Based on loan statistics, it was found that the loan for microform is not high, but the aim of this project is to ensure that the microform collection can be easily accessed by users and also to support teaching, learning and research needs at the University.